2009
DOI: 10.1007/s12665-009-0173-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical and isotopic evidence of recharge, apparent age, and flow direction of groundwater in Mayo Tsanaga River Basin, Cameroon: bearings on contamination

Abstract: Unplanned exploitation of groundwater constitutes emerging water-related threats to MayoTsanaga River Basin. Shallow groundwater from crystalline and detrital sediment aquifers, together with rain, dams, springs, and rivers were chemically and isotopically investigated to appraise its evolution, recharge source and mechanisms, flow direction, and age which were used to evaluate the groundwater susceptibility to contamination and the basin's stage of salinization. The groundwater which is Ca-Na-HCO 3 type is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 21 publications
5
33
2
Order By: Relevance
“…4, 5) may be attributed to changing conditions at the source of atmospheric moisture (Ingraham 1998;Gonfiantini et al 2001) and local climatic effects such as re-evaporation (Taupin et al 2000;Liu et al 2014). The observed slopes are similar to those reported across Cameroon (Njitchoua et al 1999;Gonfiantini et al 2001;Fantong et al 2010;Ketchemen-Tandia et al 2013;Wirmvem et al 2014;Kamtchueng et al 2015) and elsewhere in the tropics (Mbonu and Travi 1994;Gonfiantini et al 2001;Sánchez-Murillo et al 2013, 2016Rai et al 2013). The generated local meteoric water lines are useful in assessing the origin and mechanism of groundwater recharge in both localities.…”
Section: Conventional Dsupporting
confidence: 84%
See 1 more Smart Citation
“…4, 5) may be attributed to changing conditions at the source of atmospheric moisture (Ingraham 1998;Gonfiantini et al 2001) and local climatic effects such as re-evaporation (Taupin et al 2000;Liu et al 2014). The observed slopes are similar to those reported across Cameroon (Njitchoua et al 1999;Gonfiantini et al 2001;Fantong et al 2010;Ketchemen-Tandia et al 2013;Wirmvem et al 2014;Kamtchueng et al 2015) and elsewhere in the tropics (Mbonu and Travi 1994;Gonfiantini et al 2001;Sánchez-Murillo et al 2013, 2016Rai et al 2013). The generated local meteoric water lines are useful in assessing the origin and mechanism of groundwater recharge in both localities.…”
Section: Conventional Dsupporting
confidence: 84%
“…In tropical Africa, stable isotopes in precipitation are not only important in groundwater recharge studies (e.g., Mbonu and Travi 1994;Ketchemen-Tandia et al 2007;Fantong et al 2010;Wirmvem et al 2015;Adomako et al 2015). They are also useful in climatological studies including the study of atmospheric moisture circulation (Njitchoua et al 1999;Taupin et al 2000;Bony et al 2008;Risi et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chae et al (2007) confirmed that the high levels of fluoride in the groundwater in South Korea have been identified in the sedimentary aquifers that are made up of fluoride-bearing minerals derived from parent rocks of granites. Fantong et al (2010) reported that the occurrence of toxic Granites occur widely, surrounding the coastal region of Laizhou Bay, especially in the northwest part (Fig. 6).…”
Section: Sediment Characteristics Of the Aquifermentioning
confidence: 99%
“…Water is perhaps the major contributor (Chen et al 2011(Chen et al , 2012. Fluoride concentrations in water and the health problems it causes have been the subject of numerous studies in recent years (Gaciri and Davies 1993;Apambire et al 1997;Fantong et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater recharge studies in the semi-arid regions of Sub-Saharan Africa (Adanu 1991;Favreau et al 2009;Fantong et al 2010;Lutz et al 2011) and Equatorial East Africa (Nkotagu 1996;Taylor and Howard 1996;Owor et al 2009;Taylor et al 2013a, b) have reported recharge by heaviest and isotopically depleted monsoon rains. However, in groundwater recharge studies in the equatorial West Africa, recharge is by abundant but relatively less depleted rainfall events (Mbonu and Travi 1994;Oga et al 2008;Wirmvem et al 2014a).…”
Section: Introductionmentioning
confidence: 99%